The application of social philosophy in the era of revolution industry 4.0 in Indonesia - Fuad Fuad; Aida Dewi; Said Munawar (Universitas Muhammadiyah Magelang, 2022)
The presence of social philosophy is generally understood to be closely related to general philosophy. Social philosophy can see how its relation to the universe can result in interpretations of social life. Social philosophy, philosophy of science, and science itself are part of human efforts to understand a discipline's concept and method that can be implemented in changing times and progress. This study aims to examine the application of social philosophy and its relevance in the era of Industrial Revolution 4.0. This research uses a descriptive method of analysis with a literature study approach. Social philosophy is indispensable in the midst of the development of times and civilizations, such as the current era of the Industrial Revolution 4.0. By getting closer to social philosophy, it is hoped that humans can realize their limitations while cultivating an attitude and soul that is aware of the development of the times. The use of technology must benefit the welfare of all humans. So, it is hoped that it can minimize problems related to the development of technology which can change the mindset of human life to a more sophisticated life pattern. Thus, the science used as a handle in directing and controlling these developments positively for the benefit of humanity and its environment is the philosophy and social philosophy.